Comparative Evaluation of Solubilization Strategies for an ABCG2 Transporter Inhibitor - Fehér, Pálma; Kárándi, Kata; Kis, Gergő; Marminon, Christelle; Le Borgne, Marc; Józsa, Liza (De Remediis, 2026)
Poor aqueous solubility remains one of the major challenges in the development of orally administered drugs, particularly for lipophilic molecules such as ABCG2 transporter inhibitors. These compounds possess high molecular weight, significant lipophilicity, and limited water solubility, which restrict their bioavailability and therapeutic application. This study aimed to enhance the solubility of a model ABCG2 inhibitor using different solubilization techniques, including co-grinding with hydroxypropyl-β-cyclodextrin (HP-β-CD) or polyvinylpyrrolidone (PVP) and micellar solubilization using nonionic surfactants. Each formulation was optimized and characterized for drug loading, equilibrium solubility and dissolution behavior under simulated gastrointestinal conditions. The micellar formulation exhibited the highest solubilization efficiency, The HP-β-CD complex and PVP co-grinding dispersions also resulted in notable enhancement compared to the pure drug. These findings highlight the potential of simple formulation strategies to overcome solubility limitations of ABCG2 inhibitors and improve their oral bioavailability.